Social Organizations’ Embedding in Grid-Based Governance: A Resource Dependence Perspective on Pathways and Mechanisms - Jiarui Ma (International Journal of Social Sciences and Public Administration, 2026)
With the increasing complexity of grassroots governance and diversified social demands, traditional grid-based governance faces challenges such as insufficient governance resources and limited capacity for social participation. As an important actor connecting the state and society, social organizations have become increasingly involved in grassroots governance. Based on resource dependence theory, this study explores the pathways and mechanisms of social organizations’ embedding in grid-based governance. It argues that such embedding is a dynamic process driven by the interaction between governance demands and resource exchange. Specifically, social organizations achieve embedding through three interconnected processes: resource acquisition, relationship building, and functional embedding. Through providing human, professional, and social resources, social organizations complement the limitations of administrative governance, establish stable connections with grassroots governance systems, and expand governance functions in areas such as public service provision, information feedback, and governance assistance. This study provides a resource-based explanation of social organizations’ participation in grid-based governance and offers theoretical implications for promoting multi-actor participation in grassroots governance.